Correlating EFL learners’ critical thinking ability and listening comprehension strategies - Sipayung, Rohdearni Wati; Saragih, Erikson; Rumapea, Elina Lulu Bimawati (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
Even though there have been numerous studies on the use of critical thinking in language learning, research that specifically explores the relationship between critical thinking skills and listening comprehension techniques is still infrequently performed in the context of learning English in Indonesia. This study aims to reveal the correlation between EFL students' listening comprehension strategies and their critical thinking ability. Fifty Indonesian EFL students of both sexes were chosen as the study's participants to accomplish this. They were all advanced students that were chosen through cluster sampling. The Critical Thinking Questionnaire (CTQ) and the Listening Comprehension Strategies Questionnaire were the two tools used (RCSQ). On the first day, the researcher thoroughly explained the instructions for this survey and gave the participants a CTQ to assess the tactics they had used. LCSQ was delivered to them on the second day. All of the questions had to be answered within the allotted time by the participants. Fortunately, none of the students missed any of the gathered data, which will improve the accuracy of the findings. The study's conclusions showed a strong correlation between advanced EFL students' listening comprehension techniques and their capacity for critical thought. Results may be important because they help students overcome any challenges they may have with particular language abilities by identifying the tactics they use.